Consumer buying behaviour of fruit and vegetables in the Netherlands - Jassó, K. (International Journal of Horticultural Science, 2012)
The Dutch Households bought in 2010 compared with the year before a little less vegetables and less fruit. However because of a higher price level the supermarket sales of fruits and vegetables increased with 7% to almost €3 billion. A Dutch household bought 72.4 kilo fresh vegetables in 2010. This is 2% less than in 2009. Tomatoes are the most bought vegetable followed by onion and cucumber. Although the Dutch households bought less vegetables, the spending increased with 5%. The average price of vegetables was 7% higher than in 2009. In 2010 a Dutch household bought almost 88 kilo fresh fruit. Compared with 2009 this was 2% less. Apple is far out the most popular, followed by orange and banana. Also the spending on fruit decreased a little, specially on strawberry, kiwi and banana. The sales of vegetables is realized for almost 90% by the supermarket channel. Albert Heijn has a market share of 38%, followed by Superunie and C1000. Also for fruit the supermarket is the most important retail channel. However fruit is also sold for 20% in grocery stores and markets. The total turnover from supermarkets of vegetables was in 2010 over €2 billion, 8% more than in 2009. 85% of this is fresh product (fresh and pre-treated). Canned vegetables become less popular. The turnover was decreasing 2% to just under €200 million. Green beans are the most popular, followed by peas and carrots. However more money was spend on frozen vegetables (+5%) and pickles (+1%). Over 40% of the supermarket turnover of frozen vegetables is spend on spinach. The supermarket turnover of fruit increased in 2010 with 3% to €1,25 billion. From this 93% is fresh unprocessed fruit. The turnover of pre-treated (washed and sliced) is increasing, but still not more than 3%. Although with a modest share, the spending on frozen fruit also increased in 2010 to €5,5 million. The turnover of canned fruit however was decreasing with 6% compared with 2009. The supermarket turnover of pre-treated fruit was €35 million. Albert Heijn is the absolute market leader for pretreated fruit. In 2010 70% of the sales was realized by Albert Heijn. Mixed fresh pre-treated fruit, mainly fruit salads, account for 40% of the total supermarket turnover of processed fruit. Canned pineapple is the most important canned fruit in supermarkets, followed by fruit cocktail and peach. There is a high degree of awareness of consumers regarding the “must” to use enough fruit and vegetables. Despite of this, consumers do not always eat enough healthy products. Reasons for this are the busy life of the modern young people and the perception that vegetables are “not easy” to use. Therefore preparing a meal has to be easy and fast with suitable products Here is an important task for concept and product development.